Anti-Transforming Growth Factor β IgG Elicits a Dual Effect on Calcium Oxalate Crystallization and Progressive Nephrocalcinosis-Related Chronic Kidney Disease - Steiger, Stefanie; Grill, Julia Felicitas; Ma, Qiuyue; Bäuerle, Tobias; Jordan, Jutta; Smolle, Michaela; Böhland, Claudia; Lech, Maciej; Anders, Hans-Joachim (Frontiers in Immunology, 2018)
Crystallopathies are a heterogeneous group of diseases caused by intrinsic or environmental microparticles or crystals, promoting tissue inflammation and scarring. Certain proteins interfere with crystal formation and growth, e.g. with intrarenal calcium oxalate (CaOx) crystal formation, a common cause of kidney stone disease or nephrocalcinosis-related chronic kidney disease (CKD). We hypothesized that immunoglobulins can modulate calcium oxalate microcrystal formation and crystal growth and that therefore, biological IgG-based drugs designed to specifically target disease modifying proteins would elicit a dual effect on the outcome of calcium oxalate-related crystallopathies. Indeed, both the anti-TGFβ IgG and control IgG1 antibody impaired CaOx crystallization in vitro, and decreased intrarenal CaOx crystal deposition and subsequent CKD in mice on an oxalate-rich diet compared to oxalate-fed control mice. However, the TGFβ-specific IgG antibody showed nephroprotective effects beyond those of control IgG1 and substantially reduced interstitial fibrosis as indicated by magnetic resonance imaging, silver and α-SMA staining, RT-qPCR, and flow cytometry for pro-fibrotic macrophages. Suppressing interstitial fibrosis slowed the decline of GFR compared to treatment with control IgG1 (slope of m=-8.9 vs. m=-14.5 µl/min/100g BW/day, Δ=38.3%), an increased GFR at the end of the study (120.4 vs. 42.6 µl/min/100g BW, Δ=64.6%), and prolonged end stage renal disease (ESRD)-free renal survival by 10 days (Δ=38.5%). Delayed onset of anti-TGFβ IgG from day 7 was no longer effective. Our results suggest that biological drugs can elicit dual therapeutic effects on intrinsic crystallopathies, such as anti-TGFβ IgG antibody treatment inhibits CaOx crystallization as well as interstitial fibrosis in nephrocalcinosis-related CKD.